Zif-67 catalyst with core-shell heterostructure and preparation method thereof
Patent Information
- Application Number
- CN202510855719.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-25
AI Technical Summary
然而,现有催化体系在实际应用中仍面临诸多挑战:(1)催化活性位点易团聚,导致传质效率下降;(2)过渡金属离子易发生浸出,存在二次污染风险;(3)体系对pH条件敏感,适用范围有限
本发明采用了一种梯度酸处理策略,在ZIFs材料表面原位生长铁基类普鲁士蓝(PBAs)壳层,构建具有核壳结构的ZIFs@PBAs催化剂,实现协同催化以提升体系性能。该方法具备以下技术优势:(1)ZIFs核层的孔结构可调控;(2)PBAs壳层厚度可精确调控于10-100 nm范围内;(3)有利于催化活性位充分暴露。该复合催化剂在含氟有机废水的降解处理中展现出优异的催化活性与稳定性,为工业废水治理提供了全新的材料解决方案。
Smart Images

Figure CN120790231B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanomaterial synthesis technology, and in particular to a ZIF-67 catalyst with a core-shell heterostructure and its preparation method. Background Technology
[0002] With the rapid development of the battery industry, the problem of fluorinated organic pollutant (FOB) pollution has become increasingly serious. Because these pollutants contain high-energy CF bonds, their structures are stable and difficult to remove effectively by conventional physical adsorption or biodegradation methods. They remain in water for extended periods and undergo bioaccumulation, increasing their potential toxicity through the food chain. They exhibit strong carcinogenic and mutagenic properties, seriously threatening ecosystems and human health. Therefore, there is an urgent need to develop efficient, stable, and environmentally friendly targeted degradation technologies to achieve the effective treatment of these organic fluorine pollutants.
[0003] Currently, the main treatment technology for organic pollutants is advanced oxidation processes (AOPs), among which the persulfate (PMS) activation system catalyzed by transition metals has strong application prospects. However, existing catalytic systems still face many challenges in practical applications: (1) the catalytic active sites are prone to aggregation, leading to a decrease in mass transfer efficiency; (2) transition metal ions are prone to leaching, posing a risk of secondary pollution; (3) the system is sensitive to pH conditions, limiting its applicability. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for preparing ZIF-67 catalyst with a core-shell heterostructure, aiming to solve the technical problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention provides a method for preparing a ZIF-67 catalyst with a core-shell heterostructure, comprising the following steps: S10, C4H6N2 and Co(NO3)2·6H2O are added to the first mixed solution composed of water and alcohol, and stirred to dissolve to obtain solution A; S20, C4H6N2 and K3[Fe(CN)6] are added to a second mixed solution composed of water and alcohol, and stirred to dissolve to obtain solution B; S30, Stir the solution A and the solution B to allow the solution A and the solution B to react; S40, during the reaction of solution A and solution B, HCl is added dropwise to adjust the pH value of the reaction system; S50, the solutions A and B continue to react, and the catalyst product is obtained by centrifugation; S60, the catalyst product is washed alternately with water and alcohol, and then the washed catalyst product is dried. After the catalyst product is dried, it is collected to obtain the ZIF-67 catalyst with a core-shell heterostructure.
[0006] According to one aspect of the above technical solution, in step S10, the mass ratio of Co(NO3)2·6H2O to C4H6N2 is 1:(10~50), and the volume ratio of water to alcohol is 5:1~1:1.
[0007] According to one aspect of the above technical solution, in step S20, the mass ratio of K3[Fe(CN)6] to C4H6N2 is 0.1 to 0.4; the volume ratio of water to alcohol is 1:1 to 1:5.
[0008] According to one aspect of the above technical solution, in step S30, the stirring speed of solution A and solution B is 400~700 rpm, and the stirring time is 0.5h~3h.
[0009] According to one aspect of the above technical solution, in step S40, the concentration of HCl is 6 mol / L, and the volume ratio of HCl to water in step S10 is 1:50 to 1:100.
[0010] According to one aspect of the above technical solution, in step S40, the HCl is dripped in using a syringe at a dripping rate of 2-30 drops / min.
[0011] According to one aspect of the above technical solution, in step S50, the reaction time of solution A and solution B is 2 hours, the centrifugation speed is 6000 rpm to 1000 rpm, and the centrifugation time is 5 min to 15 min.
[0012] According to one aspect of the above technical solution, in step S60, the washed catalyst product is dried in a vacuum drying oven, the temperature of which is 50℃~70℃ and the drying time is 10h~18h.
[0013] According to one aspect of the above technical solution, in step S60, the catalyst product is washed three times alternately with water and alcohol.
[0014] The present invention also provides a ZIF-67 catalyst with a core-shell heterostructure, which is prepared by the method described above for preparing a ZIF-67 catalyst with a core-shell heterostructure.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention employs a gradient acid treatment strategy to grow an iron-based Prussian blue (PBAs) shell in situ on the surface of ZIFs materials, constructing a ZIFs@PBAs catalyst with a core-shell structure to achieve synergistic catalysis and improve system performance. This method has the following technical advantages: (1) the pore structure of the ZIFs core layer is tunable; (2) the thickness of the PBAs shell layer can be precisely controlled within the range of 10-100 nm; and (3) it facilitates the full exposure of catalytic active sites. This composite catalyst exhibits excellent catalytic activity and stability in the degradation treatment of fluorinated organic wastewater, providing a novel material solution for industrial wastewater treatment. Attached Figure Description
[0016] Figure 1 The images shown are SEM (ac) and TEM (df) images of ZIFs@PBAs1~3 in this embodiment of the invention. Figure 2 This is a degradation diagram of ZIFs@PBAs-2 at different temperatures in an embodiment of the present invention; Figure 3 This is a graph showing the degradation of FA under different ZIFs@PBAs-2 dosages in an embodiment of the present invention; Figure 4 This is a graph showing the degradation efficiency of ZIFs@PBAs-2 for different concentrations of FA in the embodiments of the present invention; Figure 5 This is a graph showing the concentration curves of FA before and after degradation after 5 cycles in an embodiment of the present invention. The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation
[0017] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Several embodiments of the invention are illustrated in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete.
[0018] It should be noted that when a component is said to be "fixed to" another component, it can be directly on the other component or there may be an intervening component. When a component is said to be "connected to" another component, it can be directly connected to the other component or there may be an intervening component. The terms "vertical," "horizontal," "left," "right," and similar expressions used in this document are for illustrative purposes only.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0020] Please see Figures 1 to 5 The figure shows a method for preparing the ZIF-67 catalyst with a core-shell heterostructure in the first embodiment of the present invention, which includes the following steps: S10, C4H6N2 and Co(NO3)2·6H2O are added to the first mixed solution composed of water and alcohol, and stirred to dissolve to obtain solution A; S20, add C4H6N2 and K3[Fe(CN)6] to a second mixed solution composed of deionized water and ethanol, and stir to dissolve to obtain solution B; S30, Stir the solution A and the solution B to allow the solution A and the solution B to react; S40, during the reaction of solution A and solution B, HCl is added dropwise to adjust the pH value of the reaction system; S50, the solutions A and B continue to react, and the catalyst product is obtained by centrifugation; S60, the catalyst product is washed alternately with water and alcohol, and then the washed catalyst product is dried. After the catalyst product is dried, it is collected to obtain the ZIF-67 catalyst with a core-shell heterostructure.
[0021] Understandably, this invention employs a gradient acid treatment strategy to grow an iron-based Prussian blue (PBAs) shell in situ on the surface of ZIFs materials, constructing a ZIFs@PBAs catalyst with a core-shell structure to achieve synergistic catalysis and improve system performance. This method has the following technical advantages: (1) the pore structure of the ZIFs core layer is tunable; (2) the thickness of the PBAs shell layer can be precisely controlled within the range of 10-100 nm; and (3) it facilitates the full exposure of catalytic active sites. This composite catalyst exhibits excellent catalytic activity and stability in the degradation treatment of fluorinated organic wastewater, providing a novel material solution for industrial wastewater treatment.
[0022] The water can be deionized water or ultrapure water, and the alcohol can be methanol or ethanol. In this embodiment, deionized water is used and ethanol is used.
[0023] Further, in step S10, the mass ratio of Co(NO3)2·6H2O to C4H6N2 is 1:(10~50), and the volume ratio of deionized water to ethanol is 5:1~1:1. Under the action of a magnetic stirrer, the mixture is continuously stirred at an appropriate speed until the solute is completely dissolved, thereby obtaining a homogeneous and stable solution A. During this process, C4H6N2 acts as a ligand molecule, and the lone pair electrons of its nitrogen atom coordinate with cobalt ions to form a stable complex. The addition of ethanol optimizes the solubility and dispersibility of the solution, promoting a more uniform synthesis of the catalyst. Specifically, in this embodiment, 0.6g of Co(NO3)2·6H2O and 10g of C4H6N2 are used, the volume of deionized water is 200mL, the volume of ethanol is 50mL, and the stirring speed is 400rpm.
[0024] Further, in step S20, the mass ratio of K3[Fe(CN)6] to C4H6N2 is 0.1~0.4; the volume ratio of deionized water to ethanol is 1:1~1:5. In this embodiment, 0.2g of K3[Fe(CN)6] and 10g of C4H6N2 are used, the volume of deionized water is 30mL, and the volume of ethanol is 30mL.
[0025] Understandably, the solution is fully dissolved under magnetic stirring until a homogeneous and transparent solution is obtained, which is solution B. K3[Fe(CN)6] is a key precursor for the subsequent construction of PBA shells, and its uniform dispersion in solution has a decisive influence on the structural integrity and catalytic performance consistency of the final product.
[0026] Furthermore, in step S30, the stirring speed of solution A and solution B is 400~700 rpm, and the stirring time is 0.5h~3h.
[0027] Understandably, solution B was slowly and uniformly added dropwise to solution A, and then the mixture was immediately placed on a magnetic stirrer and stirred continuously at 600 rpm for 0.5 h. During this process, the coordination structure formed by cobalt ions leached from solution A and C4H6N2 reacted synergistically with K3[Fe(CN)6] in solution B, gradually generating the precursor structure of the ZIFs67@PBAs composite material. Precise control of stirring speed and reaction time plays a crucial role in the sufficiency of the reaction and the uniformity of the product structure.
[0028] Further, in step S40, the concentration of HCl is 6 mol / L, the volume ratio of HCl to water in step S10 is 1:50 to 1:100, and the HCl is added dropwise using a syringe at a rate of 2 to 30 drops / min. In step S40, the volume of HCl is 2.5 mL, and the drop rate is 15 drops / min.
[0029] Understandably, the introduction of HCl can achieve the following functions: (1) regulating the structure of the ZIF-67 precursor through chemical etching, promoting the leaching of Co ions from the framework; (2) systematically regulating the pH microenvironment of the reaction system; and (3) inducing directional nucleation growth of PBAs on the outer surface of ZIFs. The difference in the amount of HCl added will have a significant impact on the microstructure and performance of the catalyst. Therefore, by precisely controlling its addition amount, the catalyst structure can be effectively regulated and the catalytic performance optimized. After the HCl is added, the reaction is stirred for 2 hours to ensure that the reaction proceeds fully and promotes the formation of the core-shell structure catalyst. In this embodiment, the HCl dropping rate is 15 drops / min.
[0030] Further, in step S50, the reaction time of solution A and solution B continues for 2 hours, the centrifugation speed is 6000 rpm to 1000 rpm, and the centrifugation time is 5 min to 15 min. In step S60, the washed catalyst product is dried in a vacuum drying oven at a temperature of 50℃ to 70℃ for 10 h to 18 h. In step S60, the catalyst product is washed three times alternately with deionized water and ethanol.
[0031] Understandably, after the reaction is complete, the reaction mixture is transferred to a centrifuge tube and centrifuged at 6000–10000 rpm for 5–15 min to achieve solid-liquid separation and obtain catalyst precipitate. Subsequently, the precipitate is washed multiple times with alternating deionized water and anhydrous ethanol, centrifuged at the same speed for 10 min after each wash to thoroughly remove residual impurity ions and unreacted substances from the reaction system, further improving catalyst purity. After washing, the obtained precipitate is placed in a vacuum drying oven at 60°C for 12 h to ensure complete evaporation of water and organic solvents, ultimately obtaining the ZIFs@PBAs catalyst. During the drying process, temperature and time should be strictly controlled to prevent damage to the catalyst structure. In this embodiment, the centrifugation speed is 8000 rpm, the vacuum drying oven temperature is 60°C, and the drying time is 12 h.
[0032] The preparation method proposed in this invention has a significant advantage in process simplicity: it does not rely on high-precision reaction equipment or complex chemical unit operations, but can be completed using only basic experimental operations such as conventional stirring, magnetic stirring, and centrifugation. Specifically, the preparation process achieves the self-assembly of materials through stepwise liquid-phase reaction, and the operation steps include: (1) precise proportioning of precursor solution; (2) magnetic stirring under controllable pH conditions (3 ~ 8). The entire preparation process has good controllability of process parameters and excellent batch repeatability, and is feasible for direct scaling up to pilot-scale, significantly reducing the technical threshold for industrialization.
[0033] The present invention proposes a method for preparing a ZIF-67 catalyst with a core-shell heterostructure. This method achieves effective exposure of catalytic active sites, release of metal components, and controllable adjustment of catalyst structural parameters (such as pore size distribution, surface charge density, and catalytic performance) by quantitatively introducing HCl solutions of different volumes and concentration gradients into the reaction system. In environmental remediation applications, this catalyst exhibits significant degradation capabilities for organic pollutants.
[0034] In summary, the preparation method of the ZIF-67 catalyst with a core-shell heterostructure in the above embodiments of the present invention exhibits excellent catalytic activity and stability in the degradation treatment of fluoride-containing organic wastewater, providing a novel material solution for industrial wastewater treatment.
[0035] The preparation method of the ZIF-67 catalyst with a core-shell heterostructure provided in the second embodiment of the present invention differs from that in the first embodiment in that: In step S40, the volume of HCl is 4 mL.
[0036] This invention also provides a comparative example to compare with the first and second embodiments. The comparative example provides a method for preparing a ZIF-67 catalyst with a core-shell heterostructure, which differs from the first and second embodiments in that, in step S40, HCl is not added but the mixture is directly centrifuged. The catalyst prepared by the method in the comparative example is named ZIFs@PBAs-1, the catalyst prepared by the method in the first embodiment is named ZIFs@PBAs-2, and the catalyst prepared by the method in the second embodiment is named ZIFs@PBAs-3.
[0037] The performance of catalysts prepared by the methods in the comparative example, the first example, and the second example was compared through experiments. Under the conditions of an initial FA concentration of 10 ppm, a PMS and catalyst dosage of 0.4 g / L, and the same catalytic reaction, ZIFs@PBAs-2 prepared in the second example exhibited the best catalytic activity, achieving complete degradation of FA (100%) within 20 min. ZIFs@PBAs-3 prepared in Example 3 followed, with a FA degradation efficiency of 85% within 20 min; while ZIFs@PBAs-1 prepared in Example 1 showed the worst degradation effect, degrading only 60% of the FA within the same time period. The experimental results indicate that the amount of HCl has a significant impact on both the structure and performance of the catalyst. Insufficient HCl dosage may lead to a solid catalyst structure, resulting in decreased mass transfer efficiency and a limited number of active sites, thus reducing catalytic activity. Conversely, excessive HCl dosage may cause partial dissolution of the material structure, forming a hollow structure, impairing the synergistic effect and ultimately reducing the overall catalyst activity. Therefore, rationally controlling the amount of HCl added is a key factor in achieving high-efficiency catalytic performance.
[0038] The preparation method of the ZIF-67 catalyst with a core-shell heterostructure provided in the third embodiment of the present invention differs from that in the first embodiment in that: In step S10, the mass of Co(NO3)2·6H2O is 0.2g.
[0039] The preparation method of the ZIF-67 catalyst with a core-shell heterostructure provided in the fourth embodiment of the present invention differs from that in the first embodiment in that: In step S10, the mass of Co(NO3)2·6H2O is 1.0g.
[0040] Comparison of FA degradation performance of catalysts in the first, third, and fourth embodiments: Under the conditions of an initial FA concentration of 10 ppm and a PMS and catalyst dosage of 0.4 g / L, the performance of catalysts prepared differently was compared. Under the same catalytic reaction conditions, the ZIFs@PBAs-2 prepared in the first embodiment exhibited the best catalytic performance, achieving complete FA degradation within 20 min. The material prepared in the fourth embodiment was the second best, with a degradation efficiency of 88% within 20 min; while the material prepared in the third embodiment had the worst catalytic performance, degrading only 78% of the FA within 20 min. The experimental results show that the dosage of Co(NO3)2·6H2O has a significant impact on the catalyst structure and final catalytic performance. An appropriate amount of Co precursor helps to construct a reasonable core-shell structure and generate abundant synergistic active sites, thereby effectively promoting PMS activation and FA degradation. However, excessive Co precursor may lead to structural defects or leaching of transition metal ions, not only reducing catalytic stability but also potentially causing secondary pollution.
[0041] The method for preparing the ZIF-67 catalyst with a core-shell heterostructure provided in the fifth embodiment of the present invention differs from that in the first embodiment in that: In step S20, the mass of K3[Fe(CN)6] is 0.1g.
[0042] The method for preparing the ZIF-67 catalyst with a core-shell heterostructure provided in the sixth embodiment of the present invention differs from that in the first embodiment in that: In step S20, the mass of K3[Fe(CN)6] is 0.4g.
[0043] The performance differences between the first, fifth, and sixth embodiments were compared under the conditions of an initial FA concentration of 10 ppm and PMS and catalyst dosages of 0.4 g / L. The results showed that the first embodiment still exhibited the best catalytic effect, achieving complete FA degradation (100%) within 20 min. The material of the fifth embodiment showed a FA degradation efficiency of 78% within 20 min, while the material of the sixth embodiment was significantly weaker, degrading only 50% of the FA. The experimental results indicate that the dosage of K3[Fe(CN)6] has a significant impact on the catalyst structure and final catalytic performance. The thickness of the shell can be controlled by adjusting the dosage of K3[Fe(CN)6]. When the dosage of K3[Fe(CN)6] is 0.1 g, the average shell thickness is 10 nm; when the dosage is 0.2 g, the average shell thickness is 50 nm; and when the dosage is 0.4 g, the average shell thickness is 100 nm. An appropriate amount of Fe precursor helps to construct the shell thickness, ensuring structural stability and generating abundant synergistic active sites. Therefore, rationally controlling the Co / Fe precursor ratio and structural design is key to achieving efficient and stable catalytic performance.
[0044] Figure 1 For the structural comparison of ZIFs@PBAs prepared in the comparative example, the first embodiment, and the second embodiment: Figure 1 a–c are scanning electron microscope (SEM) images, showing the surface morphology of nanomaterials obtained under different preparation conditions. Figure 1 As shown in a, ZIFs@PBAs-1 exhibits a regular polyhedral structure with uniform particle size distribution and a size of approximately 500 nm. Figure 1 The relatively rough surface of the ZIFs@PBAs-2 material in b may be due to changes in surface modification or internal structure; while Figure 1 The ZIFs@PBAs-3 shown in c has a significantly different overall morphology from the previous two, and its partially fragmented morphology indicates that it has a hollow internal structure. Figure 1 The transmission electron microscope (TEM) images from df further reveal the internal microstructure features of the material. Figure 1 As shown in d, the ZIFs@PBAs-1 particles have clear outlines and uniform internal structure; Figure 1 e exhibits typical core-shell or multilayer structure characteristics. Figure 1 f indicates the hollow structure of ZIFs@PBAs-3. This confirms the effect of different HCl dosages on the structure of the catalyst material.
[0045] Figure 2The effect of temperature on the degradation efficiency of ZIFs@PBAs-2 was investigated. The initial FA concentration was 10 ppm, the PMS to reaction solution mass-to-volume ratio was 0.4 g / L, and the ZIFs@PBAs-2 dosage to reaction solution mass-to-volume ratio was also 0.4 g / L. Figure 2 As shown, when the temperature was controlled at 15℃, 25℃, and 35℃ respectively, the removal rates of FA at 6 min were 93%, 97%, and 99%, respectively, indicating that the higher the temperature, the stronger the catalyst's ability to activate PMS.
[0046] Figure 3 The effect of ZIFs@PBAs-2 on degradation efficiency was studied. The initial FA concentration was 10 ppm, the PMS to reaction solution mass-to-volume ratio was 0.4 g / L, the temperature was 15 ℃, and the ZIFs@PBAs-2 dosages were 0.2 g / L, 0.4 g / L, and 0.6 g / L, respectively. The degradation efficiency of FA was as follows: Figure 3 As shown in the figure, the experimental results indicate that the catalytic efficiency is highest when 0.6 g / L of catalyst is added, reaching 100% removal rate after 10 minutes, while the removal rate of 0.4 g / L catalyst only reaches about 61% in the same time. Therefore, the removal rate of BPA gradually increases with the increase of catalyst dosage.
[0047] Figure 4 The effect of different initial FA concentrations on degradation efficiency was investigated. The mass-to-volume ratio of PMS to reaction solution was 0.4 g / L, the mass-to-volume ratio of ZIFs@PBAs-2 to reaction solution was 0.4 g / L, the temperature was 15℃, and the reaction solution volume was 50 mL. Figure 4 As shown, when the initial concentration of FA in the wastewater was 5 ppm, 10 ppm, and 20 ppm, the final removal rates of BPA were 97%, 93%, and 65%, respectively. The experimental results indicate that the lower the initial concentration of BPA, the better the degradation effect.
[0048] Figure 5 The figure shows the test results of five consecutive cyclic catalytic experiments on the catalyst material. The initial FA concentration was 10 ppm, the PMS to reaction solution mass-to-volume ratio was 0.4 g / L, the ZIFs@PBAs-2 dosage was 0.4 g / L, and the temperature was 15 ℃. From... Figure 5 As can be seen, the ZIFs@PBAs-2 catalytic material exhibits excellent degradation performance in each cycle, with only a slight performance decline observed in the last cycle, indicating that the constructed catalytic material has good reusability.
[0049] Among them, ZIFs67@PBAs-2 achieved a degradation efficiency of up to 100% in a simulated 4-fluoroaniline (FA) wastewater system, outperforming traditional catalysts. After five cycles of use, the catalytic efficiency remained above 80%, demonstrating excellent reusability and stability, providing solid technical support for its practical industrial applications. This achievement provides important material foundations and technical support for the green transformation and sustainable development of the chemical industry.
[0050] The seventh embodiment of the present invention provides a ZIF-67 catalyst with a core-shell heterostructure, which is prepared by the preparation method of the ZIF-67 catalyst with a core-shell heterostructure in the first embodiment.
[0051] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0052] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. The application of a ZIF-67 catalyst with a core-shell heterostructure in the degradation treatment of fluoride-containing organic wastewater, characterized in that, The ZIF-67 catalyst grows an iron-based Prussian blue shell in situ on the surface of ZIFs material. The preparation method of the ZIF-67 catalyst includes the following steps: S10, C4H6N2 and Co(NO3)2·6H2O are added to the first mixed solution composed of water and alcohol, and stirred to dissolve to obtain solution A; S20, C4H6N2 and K3[Fe(CN)6] are added to a second mixed solution composed of water and alcohol, and stirred to dissolve to obtain solution B; S30, Stir the solution A and the solution B to allow the solution A and the solution B to react; S40, during the reaction of solution A and solution B, HCl is added dropwise to adjust the pH value of the reaction system; S50, the solutions A and B continue to react, and the catalyst product is obtained by centrifugation; S60, the catalyst product is washed alternately with water and alcohol, and then the washed catalyst product is dried. After the catalyst product is dried, it is collected to obtain the ZIF-67 catalyst with a core-shell heterostructure. In step S10, the mass ratio of Co(NO3)2·6H2O to C4H6N2 is 1:(10~50), and the volume ratio of water to alcohol is 5:1~1:1; In step S20, the mass ratio of K3[Fe(CN)6] to C4H6N2 is 0.1 to 0.4; the volume ratio of water to alcohol is 1:1 to 1:
5.
2. The application of the ZIF-67 catalyst with a core-shell heterostructure according to claim 1 in the degradation treatment of fluoride-containing organic wastewater, characterized in that, In step S30, the stirring speed of solution A and solution B is 400~700 rpm, and the stirring time is 0.5h~3h.
3. The application of the ZIF-67 catalyst with a core-shell heterostructure according to claim 1 in the degradation treatment of fluoride-containing organic wastewater, characterized in that, In step S40, the concentration of HCl is 6 mol / L, and the volume ratio of HCl to water in step S10 is 1:50 to 1:
100.
4. The application of the ZIF-67 catalyst with a core-shell heterostructure according to claim 1 in the degradation treatment of fluoride-containing organic wastewater, characterized in that, In step S40, the HCl is dripped in using a syringe at a rate of 2-30 drops / min.
5. The application of the ZIF-67 catalyst with a core-shell heterostructure according to claim 1 in the degradation treatment of fluoride-containing organic wastewater, characterized in that, In step S50, the reaction time of solution A and solution B is 2 hours, the centrifugation speed is 6000 rpm to 1000 rpm, and the centrifugation time is 5 min to 15 min.
6. The application of the ZIF-67 catalyst with a core-shell heterostructure according to claim 1 in the degradation treatment of fluoride-containing organic wastewater, characterized in that, In step S60, the washed catalyst product is dried in a vacuum drying oven at a temperature of 50°C to 70°C for 10 to 18 hours.
7. The application of the ZIF-67 catalyst with a core-shell heterostructure according to claim 1 in the degradation treatment of fluoride-containing organic wastewater, characterized in that, In step S60, the catalyst product is washed three times with alternating water and alcohol.
Citation Information
Patent Citations
Method for improving specific capacity of Prussian blue through effective etching agent surface etching
CN117383584A